Teologiczne rozumienie Tradycji - Ciećko, Szymon Krzysztof (Studia Theologica Varsaviensia, 2020)
The article presents the issue of Tradition in the understanding of Catholic theology. It starts from the definition of tradition in general and then presents the theological understanding of Tradition in relation to the person of Jesus Christ and bearers of Tradition, above all the Church as the People of God and the Magisterium. Finally, selected council rulings are analyzed in which the subject of Tradition is raised in its relation to the Holy Scriptures.